The effect of a field with teachers in theory and training of etnógrafo - Telmo Humberto Lapa Caria (Universidade Federal de Santa Catarina, 2008)
This article discusses the use and meaning that teachers in the context of their work, or could attach allocate the abstract knowledge they had gained access to their processes of formal education.